Pengaruh Beban Kerja pada Masa Pandemi Covid-19 terhadap Kinerja Petugas PT. Gapura Angkasa Di Bandar Udara Internasional Husein Sastranegara - Raka Putra Pratama (Formosa Journal of Multidisciplinary Research, 2022)
The results of research conducted at the company PT. The sky gate at Hussein Sastranegara International Airport shows  that there is an influence between workload on officer performance. From the results of linear regression analysis, it can be explained that the increase and decrease in the performance of an officer is not all influenced by the workload but there are other variables that can affect the performance of the officer. Based on the results of the research obtained by the researchers that the results of the workload have a negative and significant effect on the performance of officers, so if the workload of officers increases, it will potentially decrease the performance of officers and vice versa if the workload decreases, it will potentially increase the performance of officers.